Answer:
Simplifying
(x + -2) * 2 + (y + -4) * 2 = 36
Reorder the terms:
(-2 + x) * 2 + (y + -4) * 2 = 36
Reorder the terms for easier multiplication:
2(-2 + x) + (y + -4) * 2 = 36
(-2 * 2 + x * 2) + (y + -4) * 2 = 36
(-4 + 2x) + (y + -4) * 2 = 36
Reorder the terms:
-4 + 2x + (-4 + y) * 2 = 36
Reorder the terms for easier multiplication:
-4 + 2x + 2(-4 + y) = 36
-4 + 2x + (-4 * 2 + y * 2) = 36
-4 + 2x + (-8 + 2y) = 36
Reorder the terms:
-4 + -8 + 2x + 2y = 36
Combine like terms: -4 + -8 = -12
-12 + 2x + 2y = 36
Solving
-12 + 2x + 2y = 36
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation.
-12 + 2x + 12 + 2y = 36 + 12
Reorder the terms:
-12 + 12 + 2x + 2y = 36 + 12
Combine like terms: -12 + 12 = 0
0 + 2x + 2y = 36 + 12
2x + 2y = 36 + 12
Combine like terms: 36 + 12 = 48
2x + 2y = 48
Add '-2y' to each side of the equation.
2x + 2y + -2y = 48 + -2y
Combine like terms: 2y + -2y = 0
2x + 0 = 48 + -2y
2x = 48 + -2y
Divide each side by '2'.
x = 24 + -1y
Simplifying
x = 24 + -1y
Explanation: